Records of violence against women at the Legal Medical Institute in Lages, in the State of Santa Catarina, Brazil, from 2004 to 2012 (Research, Society and Development, 2020)
Violence is a problem for all segments of society. In Brazil, the notification of violence against women is a legal requirement, the result of an ongoing struggle to ensure that the violence perpetrated against this segment of the population leaves the political invisibility and the little social legitimacy that is sometimes attributed to it. The General Institute of Forensics (GIF) is an official expert body, with competences, among other things, for carrying out criminal investigations. Its member is the Legal Medical Institute (LMI), responsible for autopsies, cadaveric reports, examination of bodily injuries; intoxication or intoxication by substance of any kind; of finding sexual violence; mental health, sexually transmitted infection, and all other expertise that requires the opinion of specialists in Forensic Medicine. The objective is to identify how many records of violence against women there were between the years 2004 to 2012. A quantitative survey was carried out at the LMI in the municipality of Lages (SC). The records were searched in the body examination book. In all years, the minor injury was registered by the coroner in over 65% of the cases. The role of Organs legal, social, educational and health agencies in forming a network will allow violence against women to leave the cloak of invisibility and be extinguished from societies. That is why it is necessary to work together to eliminate the domination of the masculine over the feminine, and it must involve the public and the private in the fight against this extinction.